Tailoring EFL lessons through materials adaptation: A look into an Acehnese teacher's experiences - Hanifa, Rizaldy; Yusra, Siti Rahimah (LingTera, 2023)
This study focused on teachers' materials adaptation as a part of teaching strategies to ensure learning success. Given that such activity is not something light to engage in and requires expertise, the researchers looked at how the process of materials adaptation was carried out. These included what was added, removed, and modified as well as the challenges confronted during the adaptation process and classroom implementation. This study sought perspective from a qualitative case study approach. Documents, classroom observations, and interview were employed to gather data from one senior high school teacher in Aceh, Indonesia. The results were analyzed based on frameworks of language teaching materials analysis, principles of teaching materials, and materials adaptation. Research findings suggested that materials adaptations mostly concentrated on adding and modifying, with less emphasis on eliminating, simplifying, and rearranging. Furthermore, the altered materials aided language learning in various ways. Nevertheless, several modifications made raised issues, such as the lack of a feeling-sharing session with the materials and an inappropriate difficulty level. Inaccessible sources of materials, fear of producing irrelevant information, time constraints, a lack of professional training and school assistance, learners' uncooperative behavior and low competences were also identified as problems in materials adaption.